Differential growth response of green and variegated Ficus benjamina to exogenous cytokinin and shade - Di Benedetto, Adalberto; Galmarini, Claudio Romulo; Tognetti, Jorge (Sociedade Brasileira de Floricultura e Plantas Ornamentais, 2022)
Benjamin fig (Ficus benjamina) is an important foliage and landscape crop species comprising green and variegated genotypes. The latter develop leaves with yellow and white leaf areas which may impose lower photosynthetic activity, thus resulting in slower growth than green genotypes. In many species, the exogenous supply of cytokinin to pot-grown plants promotes growth, mainly due to enhanced carbon fixation. In this work, we analyze the effect of spraying the cytokinin 6-benzylaminopurine (BAP) on growth and development of green and variegated Ficus benjamina genotypes. Two experiments were carried out in a greenhouse, in which either different number of BAP applications (Experiment 1) or different BAP concentrations (Experiment 2) were tested. In Experiment 2, plants were grown under three different light intensities. BAP sprays promoted rate of leaf appearance, leaf expansion and whole-plant growth, and the effect was stronger in variegated than in green plants. The relative growth rate promotion by BAP was associated with increased net assimilation rate rather than with variation in the leaf area ratio. On the other hand, shading had a more negative impact on growth and development of variegated plants than in green ones. Variegated plants, unlike green ones, developed leaves with high specific leaf area under the lowest light intensity. This led to high leaf area ratio values, which helped to maintain relative growth rates close to those of plants under moderate shading.